Meningkatkan Hasil Belajar IPA Melalui Model Experiental Learning - Dumaria Hutapea (JURNAL GLOBAL EDUKASI, 2022)
Abstract: The purpose of this study was to determine the increase in learning outcomes of sixth grade students at SD Negeri 010039 Sentang, Kisaran Timur sub-district, Asahan district for the 2019/2020 school year on the concept of heat energy through learning to find concepts with experiential learning models. This study uses a classroom action research design (CAR) with an increase in design elements that allow an overview of the effectiveness of the learning carried out to be obtained. At the end of the study, the results of the final assessment were obtained with an average correct answer of 87.6% and an average completeness of 100%. This means that when compared to cycle I, in cycle II there was an increase in the percentage of correct answers by 6%, as well as in other aspects, namely: natural knowledge skills increased by 2%. Keywords: experiential learning; concept discovery  Abstrak: Tujuan penelitian ini adalah untuk mengetahui peningkatan hasil belajar siswa  kelas VI SD Negeri 010039 Sentang kecamatan Kisaran Timur labupaten Asahan tahun pelajaran 2019/2020 pada konsep energi panas melalui belajar menemukan konsep dengan model experiential learning. Penelitian ini menggunakan rancangan penelitian tindakan kelas (PTK) dengan peningkatan pada unsur desain yang memungkinkan diperolehnya gambaran keefektifan pembelajaran yang dilakukan. Pada akhir pembelajaran diperoleh hasil penilaian akhir dengan rata-rata jawaban benar 87,6% dan rata-rata ketuntasan 100%. Berarti jika dibanding siklus I, pada siklus II ada peningkatan prosentase jawaban benar sebesar 6%, begitu pula pada aspek-aspek lain yaitu: ketrampilan pengetahuan alam naik 2%. Kata Kunci: experiential learning; penemuan konsep